Inter-relações entre nematoides, fungo e a cultura da seringueira - Takahashi, Vanessa dos Santos Paes [UNESP] (2015)
The heveiculture plays an important hole in São Paulo State, which produces more than 50% of the total Brazilian natural rubber production. The nematodes are important pathogens that have been causing significant losses to the crops. In the literature there is not many papers related to nematodes in rubber trees, especially about Pratylenchus brachyurus, the nematode most important to Brazil nowadays. In this sense the objectives of this work were: a) to do a survey of the nematodes occurrence in rubber trees nurseries in São Paulo State, b) study the resistance and tolerance of rubber trees used as rootstock to Pratylenchus brachyurus and Meloidogyne exigua, c) study the interactions between M. exigua or P. brachyurus, and Lasiodiplodia theobromae in rubber trees seedlings in two moisture conditions. As the results of the survey it was found that Meloidogyne and Pratylenchus were the most frequent and in high densities at the samples. The species identified were M. incognita, M. exigua, P. brachyurus e R. reniformis. Among them, P. brachyurus was the most frequent specie found at rubber trees roots and must be consider as a key nematode to the crop. This work was also the first report of M. exigua causing damage to the rubber trees seedlings in São Paulo State. The second experiment carried out at green house conditions, have demonstrate that M. exigua caused more pronounced damage to the rubber tree rootstocks 'GT 1', 'PB 235', 'PB 217', 'RRIM 501', 'PR 255', 'IAN 873', 'RRIM 600' e 'TJ 1', and all of them were intolerant and susceptible to M. exigua e P. brachyurus. Finally, at the third experiment also carried out in green house conditions, was observed that the biometrics characteristics and the nematodes were affected by the reduction in 50% (CC) of pot capacity. There was an interaction between L. theobromae and P. brachyurus in the increase of plant diameter. There was not an interaction among ...